Development of Illustrated Interactive Basic Literacy Media to Enhance Early Grade Students’ Writing Skills - Alaida fitri; Ahmad Calam; Fatmawati Fatmawati (Institut of Shanti Bhuana, 2026)
This study was conducted to develop an interactive illustrated basic literacy media that demonstrates validity, practicality, and effectiveness in improving the writing skills of lower grade elementary school students. This study uses a Research and Development (R&D) approach using ADDIE as a development model design that involves several systematic stages, including needs analysis, product design, media development, expert validation, revision, and field testing. Participants involved in this study were 21 lower grade elementary school students in Kwala Langkat Village. Data collection techniques included expert validation sheets, student response questionnaires, and writing assessments given through pretests and posttests. The feasibility of the developed media was examined using percentage-based analysis, while the improvement in students' writing performance was determined through N-Gain calculations. The results show that the interactive illustrated literacy media meets the required feasibility standards. Evaluations conducted by material and media design experts categorized the product as highly valid, indicating that the product is suitable for instructional use. In terms of practicality, students expressed very positive responses, indicating that the media is interesting and easy to use. In addition, the effectiveness test showed a significant improvement in students' writing performance, as reflected in the increase in the average score between the pre-test and post-test, with the N-Gain results classified in the moderate category. These findings indicate that the developed media can serve as an alternative instructional resource to support the development of students' basic literacy skills with an average proficiency level above 70, so it can be concluded that this media is valid, feasible, and practical to use.